HIDROPOLITIK TIONGKOK DI ASIA: PENGARUH GEOPOLITIK DAN GEOSTRATEGIS TIONGKOK TERKAIT SUMBER DAYA STRATEGIS AIR DI TIBET TERHADAP KEAMANAN AIR DI NEGARA-NEGARA RIPARIAN SUNGAI MEKONG - Ivanno Julius Reynaldi, (2022)
Tibet is an area that was annexed by China in 1950 and later became a strategic area for China's geopolitical interests. Tibet, which is the headwaters of the ten major rivers in the world that are spread throughout Asia, is no exception to the Mekong River which flows through countries in the region of Southeast Asia, where these countries also depend on the flow of the river for their domestic needs. China has formed many policies along the upstream river intending to divert the river's flow and also as a hydro political tool against the countries drained by the Mekong River. As part of China's Indo-Pacific strategy, the geopolitics of Tibet's water resources gives China the power to unilaterally exploit its geostrategy in the Tibetan Plateau and this has direct implications for riparian countries on the Mekong River, which cause water security conflicts in the form of drought as well as the scarcity of water resources. In this case study, the author writes research using qualitative-explanative research methods whose data comes from literature studies related to the topics discussed. The author would also use theories and concepts from geopolitics and geostrategy, hydropolitics, and water security to analyze the topics to be discussed. Based on the topics discussed, the author understands that Tibet is an important factor to support China's geopolitical interests in the Asian region through its hydro political strategy and then affects water security, especially for countries that are drained by the Mekong River.